Umbelliferone and Its Synthetic Derivatives as Suitable Molecules for the Development of Agents with Biological Activities: A Review of Their Pharmacological and Therapeutic Potential - Anita Kornicka; Łukasz Balewski; Monika Lahutta; Jakub Kokoszka (MDPI AG, 2023)
Umbelliferone (UMB), known as 7-hydroxycoumarin, hydrangine, or skimmetine, is a naturally occurring coumarin in the plant kingdom, mainly from the Umbelliferae family that possesses a wide variety of pharmacological properties. In addition, the use of nanoparticles containing umbelliferone may improve anti-inflammatory or anticancer therapy. Also, its derivatives are endowed with great potential for therapeutic applications due to their broad spectrum of biological activities such as anti-inflammatory, antioxidant, neuroprotective, antipsychotic, antiepileptic, antidiabetic, antimicrobial, antiviral, and antiproliferative effects. Moreover, 7-hydroxycoumarin ligands have been implemented to develop 7-hydroxycoumarin-based metal complexes with improved pharmacological activity. Besides therapeutic applications, umbelliferone analogues have been designed as fluorescent probes for the detection of biologically important species, such as enzymes, lysosomes, and endosomes, or for monitoring cell processes and protein functions as well various diseases caused by an excess of hydrogen peroxide. Furthermore, 7-hydroxy-based chemosensors may serve as a highly selective tool for Al3+ and Hg2+ detection in biological systems. This review is devoted to a summary of the research on umbelliferone and its synthetic derivatives in terms of biological and pharmaceutical properties, especially those reported in the literature during the period of 2017-2023. Future potential applications of umbelliferone and its synthetic derivatives are presented.